(untitled) (IJOVTECH, 2026)
This paper examines the effectiveness of peer led conversational practice as an instructional tool in teaching oral proficiency to secondary school learners in Ebonyi State in Nigeria. Based on the ideas of communicative language teaching and sociocultural theory, the study has the quasi-experimental design according to which it will compare the oral proficiency improvement in an experimental group that communicates peerly and the control group that is taught by a teacher in the traditional setting. A total of 120 students of four state-run secondary schools were recruited to the study using stratifxied random sampling to include a balance between the gender, age, and socioeconomic status of the respondents. Data were gathered by pre- and post-oral proficiency tests in the form of Oral Proficiency Interview (OPI) scale modified to fit the local circumstances with the help of semi-structured interviews and observation of classes. The demographics showed a balanced group of 52 male and 48 female participants aged between 14-18 years with most of them being of rural agrarian families with limited exposure to English otherwise. The outcomes showed a lot of improvements in word fluency, vocabulary, and pronunciation in the experimental group with the mean post-test scores increasing by 2.82 points to 4.54 on a 6-point scale, and a marginal gain in the control group. Paired t-tests showed that at p = 0.01 these differences were statistically significant. The results emphasize the potential of the peer-led strategy in the resource-strained EFL context, where a lack of teacher and large classes are the dominant factors. Some tips have been recommended that peer-led practices should be included in national curricula and training of teachers on facilitating practices. This research will be added to the discussion of the learner-centered approach in developing countries and focus on the peculiarities of culture and language in Ebonyi State peer-led learning, oral proficiency, communicative language teaching, Ebonyi State, Nigeria, EFL pedagogy